2017
DOI: 10.1021/acs.jpcc.7b04210
|View full text |Cite
|
Sign up to set email alerts
|

Doped Amorphous Ti Oxides To Deoptimize Oxygen Reduction Reaction Catalysis

Abstract: The oxygen reduction reaction (ORR) is a major factor that drives galvanic corrosion. To better understand how to tune materials to better inhibit catalytic ORR, we have identified an in silico procedure for predicting elemental dopants that would cause common, natively formed titanium oxides to better suppress this reaction. In this work, we created an amorphous TiO2 surface model that is in good agreement with experimental radial distribution function data and contains reaction sites capable of replicating e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 42 publications
4
23
0
Order By: Relevance
“…The bottom two layers of the slab model were fixed to the bulk structure while the top two layers were relaxed to model the reaction on the surface. Dopants were represented by substituting a top‐layer surface Sn atom with a Gd or Ni atom to predict the maximum impact of dopants on the electrocatalytic activity, analogous to prior work by a Groenenboom et al on doped TiO 2 structures 29 . and the EOP intermediates are placed to be adsorbed directly to the dopant atom for the same purpose.…”
Section: Methodsmentioning
confidence: 99%
“…The bottom two layers of the slab model were fixed to the bulk structure while the top two layers were relaxed to model the reaction on the surface. Dopants were represented by substituting a top‐layer surface Sn atom with a Gd or Ni atom to predict the maximum impact of dopants on the electrocatalytic activity, analogous to prior work by a Groenenboom et al on doped TiO 2 structures 29 . and the EOP intermediates are placed to be adsorbed directly to the dopant atom for the same purpose.…”
Section: Methodsmentioning
confidence: 99%
“…[5][6] [7]. Global costs for corrosion treatment reach 3.4% of global GDP or about US$ 2.5 trillion per year [8] [9]. The increase in these costs over the last decade has continued to increase [10].…”
Section: Introductionmentioning
confidence: 99%
“…1 Groenenboom et al revealed that the overvoltage of the ORR on Nb-doped TiO 2 is lower than that of undoped TiO 2 and the durability is as high as that of TiO 2 . 2 Yamamoto et al predicted that the onset potential of the ORR of TiO 2 doped with Pd or Rh equals to the equilibrium potential of the ORR. 3 These results suggest that TiO 2 electrodes have great potential of new cathode catalysts of fuel cells in the next generation.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 However, there have been few reports on the ORR activity of Nb-doped TiO 2 without Pt nanoparticles. 2,6 In this study, we have adopted the following three methods to improve the ORR activity of Nb-doped TiO 2 : (1) control of the surface in atomic level using single crystal electrodes, (2) modification of the surface with hydrophobic species, and (3) improvement of the conductivity by changing Nb concentration. An electrochemical reaction depends on a surface structure of the electrode; 7-10 study on the ORR activity using single crystal electrodes is effective for the elucidation of the active sites of the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%